2021
DOI: 10.1136/jmedgenet-2021-107953
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis genome-wide association study implicates AGRN as a risk locus

Abstract: BackgroundMyasthenia gravis (MG) is a rare autoimmune disorder affecting the neuromuscular junction (NMJ). Here, we investigate the genetic architecture of MG via a genome-wide association study (GWAS) of the largest MG data set analysed to date.MethodsWe performed GWAS meta-analysis integrating three different data sets (total of 1401 cases and 3508 controls). We carried out human leucocyte antigen (HLA) fine-mapping, gene-based and tissue enrichment analyses and investigated genetic correlation with 13 other… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…In addition, the genes of protein tyrosine phosphatase non-receptor type 22 protein (PTPN22), TNF receptor superfamily member 11a protein (TNFRSF11A), and HLA-DQA1/HLA-B showed MG-associated signals. A genome-wide association study including 1,401 MG patients and 3,508 healthy controls, also showed an association between HLA-DRB1/HLA-B and TNFRSF11A gene [70]. Like the previously discussed study, autoimmune diseases like type 1 diabetes, rheumatoid arthritis, late-onset vitiligo, and autoimmune thyroid disease were related to MG in this study.…”
Section: Genetic Factors In Mgsupporting
confidence: 83%
“…In addition, the genes of protein tyrosine phosphatase non-receptor type 22 protein (PTPN22), TNF receptor superfamily member 11a protein (TNFRSF11A), and HLA-DQA1/HLA-B showed MG-associated signals. A genome-wide association study including 1,401 MG patients and 3,508 healthy controls, also showed an association between HLA-DRB1/HLA-B and TNFRSF11A gene [70]. Like the previously discussed study, autoimmune diseases like type 1 diabetes, rheumatoid arthritis, late-onset vitiligo, and autoimmune thyroid disease were related to MG in this study.…”
Section: Genetic Factors In Mgsupporting
confidence: 83%
“…However in the GWAS catalog ( 41 ) FLI1 has a significant association with Vitiligo, when the onset age is not taken into account ( 42 ), and CTLA4 is found associated with different GWASs (not studied here) for both Myasthenia gravis ( 43 ) and Vitiligo ( 42 ). CTLA4 was also significant in the gene-based analysis ( 44 ) of the data we used in this meta-analysis. The gene set enrichment analysis including the genes in the significant and pleiotropic regions identified four significantly enriched GO : BP terms; bone cell development, immune system development, myeloid cell development, and immune system process ( Figure 6A ; Table S5 ).…”
Section: Resultsmentioning
confidence: 92%
“…However in the GWAS catalog (41) FLI1 has a significant association with Vitiligo, when the onset age is not taken into account (42), and CTLA4 is found associated with different GWASs (not studied here) for both Myasthenia gravis (43) and Vitiligo (42). CTLA4 was also significant in the gene-based analysis (44) of the data we used in this meta-analysis. The gene set enrichment analysis including the genes in the significant and pleiotropic regions identified four significantly enriched GO:BP terms; bone cell development, immune system development, myeloid cell development, and immune system process (Figure 6A, Table S4).…”
Section: Resultsmentioning
confidence: 92%